2011
DOI: 10.15835/nbha3926122
|View full text |Cite
|
Sign up to set email alerts
|

Seed Priming and Field Performance of Soybean (Glycine max L.) in Response to Water Limitation

Abstract: Laboratory tests and a field experiment were carried out to evaluate the effects of priming methods on seed invigoration and field performance of soybean (cv. 'Zan'). The field experiment was arranged as split plot based on RCB design with three replications. Irrigation treatments (I 1 , I 2 and I 3 : irrigation after 70, 110 and 150 mm evaporation from class A pan) and priming methods (water, 3% KH 2 PO 4 and 3% KNO 3 for 8 h at 15±1°C) were allocated to main and sub-plots, respectively. Germination percentag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 24 publications
3
5
1
Order By: Relevance
“…This may have reduced remobilization of nutrient for use in germination. Similar reduction in germination with fertilizer application has been reported by others [24].…”
Section: Seed Germinationsupporting
confidence: 90%
See 1 more Smart Citation
“…This may have reduced remobilization of nutrient for use in germination. Similar reduction in germination with fertilizer application has been reported by others [24].…”
Section: Seed Germinationsupporting
confidence: 90%
“…However, in 2014, variety and water priming and its interaction significantly ( = 0.05) affected seedling emergence (Table 4). While some studies have shown that priming with fertilizer reduces germination and emergence [24], this study showed that N fertilizer application had no effect on seedling emergence. Similarly, lack of improved field emergence of soybean with sulphur application was reported [19].…”
Section: Seedling Emergence In 2013 Except For Variety None Of Thecontrasting
confidence: 81%
“…Saeed et al (2017) found that among several techniques, including three forms of priming, that hydropriming resulted in most rapid seedling emergence, significantly improved plant density, plant height, number of pods plant -1 , 1000-seed weight, biological yield and seed yield. Seed priming using KH 2 PO 4 or KNO 3 increased mean emergence time, number of pods plant -1 and grain yield plant -1 but had no impact on 1000grain yield or harvest index (Ghassemi-Golezani et al, 2011). Moshtaghi-Khavaran et al (2015) used four classes of soybean seeds and hydroprimed them with distilled water or haloprimed them with 75 mM NaCl, finding that the latter improved the germination of large seeds more than small seeds.…”
Section: Seed Priming To Manage Salinitymentioning
confidence: 98%
“…Although the effects of cathodic water on emergence have not been tested before, priming with other solutions has been shown to improve emergence parameters. For example, priming was reported to promote the earlier emergence of seedlings in Oryza sativa [33] and Zea mays [34]. A particularly important emergence parameter is uniformity, because uniformity can improve stand establishment and increase biomass, particularly when conditions are suboptimal, such as during drought, salinity and water stress [33,34].…”
Section: Effects Of Priming On Emergencementioning
confidence: 99%
“…For example, priming was reported to promote the earlier emergence of seedlings in Oryza sativa [33] and Zea mays [34]. A particularly important emergence parameter is uniformity, because uniformity can improve stand establishment and increase biomass, particularly when conditions are suboptimal, such as during drought, salinity and water stress [33,34]. Uniformity of emergence can also reduce weed-inflicted yield loss, for example by up to 10% in rice [35].…”
Section: Effects Of Priming On Emergencementioning
confidence: 99%